Jails in Indian country, 2011 - Minton, Todd D. (Jails in Indian Country)
Presents findings from the 2011 Survey of Jails in Indian Country, an enumeration of 80 jails, confinement facilities, detention centers, and other correctional facilities operated by tribal authorities or the Bureau of Indian Affairs. This report provides trends in the number of adults and juveniles held, type of offense, number of persons confined on the last weekday in June, peak population, average daily population, admissions in June, and average expected length of stay in jail upon admission. It also provides data on rated capacity, facility crowding, and jail staffing in June 2011, and counts of inmate deaths and suicide attempts. Based on an addendum to the survey, data are also presented on inmate medical and mental health services, suicide prevention, substance dependency programs, domestic violence counseling, sex offender treatment, educational programs, and inmate work assignments. The report summarizes the total population of American Indians and Alaska Natives under correctional supervision in the U.S., including persons in correctional facilities or on probation or parole outside of Indian country.